The role of AMPK/mTOR signaling pathway in anticancer activity of metformin - Sabová, Nikola; Gažová, Andrea; Samáková, Adriana; Valaskova, S; Kyselovič, Ján (Physiological research, 2021)
Metformin (MTF) is a widely used drug for the treatment of diabetes mellitus type 2 (DM2) and frequently used as an adjuvant therapy for polycystic ovarian syndrome, metabolic syndrome, and in some cases also tuberculosis. Its protective effect on the cardiovascular system has also been described. Recently, MTF was subjected to various analyzes and studies that showed its beneficial effects in cancer treatment such as reducing cancer cell proliferation, reducing tumor growth, inducing apoptosis, reducing cancer risk in diabetic patients, or reducing likelihood of relapse. One of the MTF's mechanisms of action is the activation of adenosine-monophosphate-activated protein kinase (AMPK). Several studies have shown that AMPK/mammalian target of rapamycin (mTOR) pathway has anticancer effect in vivo and in vitro. The aim of this review is to present the anticancer activity of MTF highlighting the importance of the AMPK/mTOR pathway in the cancer process.
Keywords: proteinkinasy aktivované AMP; Animals; apoptóza; metformin; TOR Serine-Threonine Kinases; Apoptosis; Neoplasms; nádory; lidé; AMP-Activated Protein Kinases; Antineoplastic Agents; Hypoglycemic Agents; protinádorové látky; signální transdukce; Metformin; Signal Transduction; hypoglykemika; Drug Repositioning; zvířata; TOR serin-threoninkinasy; přehodnocení terapeutických indikací léčivého přípravku; Humans